OP09 Immunomodulatory mechanisms of faecal microbiota transplantation are associated with clinical response in ulcerative colitis: early results from STOP-Colitis. (15th January 2020) - Quraishi, M N; Oo, Y H; Beggs, A; Withers, D; Acharjee, A; Sharma, N; Manzoor, S; Hart, A L; Gaya, D R; Loman, N J; Hawkey, P M; Gerasimidis, K; et al.
Abstract: Background: Studies of faecal microbiota transplantation (FMT) for treating ulcerative colitis (UC) have shown promising results. Mechanisms by which FMT modulates inflammation, however, remain unexplored. Through a prospective, open-label pilot of FMT in UC (STOP-Colitis) we conducted a sub-study to explore changes in host colonic mucosal immune cell subsets and gene expression following FMT. Methods: Patients in this study received eight infusions of FMT over an 8-week period. Colon biopsies and blood were obtained at baseline and at the end of the study. Immunophenotyping of colonic lamina propria mononuclear cells (LPMC) and peripheral blood mononuclear cells (PBMC) was conducted. RNA sequencing was performed on colon biopsies for differential gene expression analysis followed by multi-omic integration. Results: Seventeen patients were recruited to this sub-study; of which, 12 completed 8 weeks of FMT per protocol. Response (reduction in MAYO score) was seen in 67% (8/12) of patients. Analysis of colonic LPMC populations revealed a significant increase in regulatory T cells (Tregs, CD4+CD25+CD127lowFoxP3+; Δ 5.02%; p < 0.01), especially effector memory Treg subset (CD4+CD25+CD127-CCR7-CD45RA-; Δ 12%; p < 0.001), gut homing Tregs (CD4+CD25+CD127-CCR7-CD45RA-α4+; Δ 18.55%; p < 0.01) and IL-10 producing CD4 cells (Δ 2.16%; p = 0.04) in responders following FMT. Along with this, there was a significant reduction in mucosal Th17 cell (CD4+CD161+CCR6+; Δ −7.61%; p = 0.017), IL-17 producing CD4 cell (Δ −7.69%; p = 0.05) and CD8 cell (Δ -5.18%; p = 0.04) populations in FMT responders. Colonic mucosal gene expression and pathway analysis demonstrated that response to FMT was associated with significant downregulation of host antimicrobial defence response mainly REG and defensin family of anti-microbial peptides, pathogen-associated molecular pattern binding receptors, proteases, multiple MHC class II genes associated with antigen presentation and proinflammatory immune pathways. There was a significant upregulation of butanoate and propionate metabolic pathways in FMT responders. Analysis of PBMC revealed a significant increase in IL-10 producing CD4 cells suggesting that induction of peripheral immune tolerance is preferentially compartmentalised to the gut mucosa. Conclusion: Response to FMT is associated with a significant increase in mucosal gut homing Tregs and butanoate metabolism along with a reduction in Th17 cells and multiple anti-microbial defence and proinflammatory pathways. FMT induces change in immune balance in local milieu which leads to clinical response in UC. Exploring microbial mediators in FMT which influence immunometabolism is now under investigation to underpin novel biotherapeutic approaches.